Refractory Hyponatremia due to Systemic Infection: A Systematic Review - Inayah, Dinda Rifdayani; Priyanto, Bambang; Rohadi, Rohadi; Januarman, Januarman (Universitas Airlangga, 2024)
Highlight: Hyponatremia is a potentially life-threatening condition. Refracter hyponatremia can be seen in patients with systemic infection who have undergone therapy. ABSTRACT Introduction: Hyponatremia is a condition in which the sodium serum level is below the normal range. This condition is most common in hospitalized patients receiving systemic infection therapy and can lead to worse outcomes, potentially life-threatening.Objective: This study aimed to summarize the incidence of refractory hyponatremia due to systemic infection therapy. Methods: This was a systematic literature search conducted in October 2023 on the online database PubMed regarding refractory hyponatremia due to systemic. The analysis excluded narrative reviews, non-English studies, and studies that only discussed transient hyponatremia or local infections. Results: A total of 10 case reports of 11 patients were included in the final analysis. The mean age of patients was 46.63 years (SD = 20.79 years), and 63.64% were male. Strongloides stercoralis hyperinfection was the most common cause of systemic infection (54%). It was followed by disseminated Varicella-zoster virus infection (28%), tuberculosis (9%), and systemic nocardiosis (9%). The most common cause of immune compromise is stem cell transplant recipients (28%), followed by miliary tuberculosis (18%). Up to 91% of cases are caused by the syndrome of inappropriate antidiuretic hormone (SIADH), which is the pathophysiology of hyponatremia. Conclusion: Most patients with systemic infections and refractory hyponatremia have conditions that encourage immune compromise. The treatment of systemic infections is a priority since they contribute to hyponatremia.